Complete denture fractures: Insights into clinical failures and management strategies - Nadia Kartikasari; Annora OI. Nathaniela; Samuel K. Kurniawan; Fionna A. Putri; Hilaria R. Irawan; Ratri M. Sitalaksmi; Karina Mundiratri; Abil Kurdi (Indonesian Journal of Prosthodontic, 2025)
Background: Complete denture fractures are a common complication in edentulous patients, mainly due to a combination of anatomical, biomechanical, material, and technical factors. This condition affects masticatory function, comfort, and quality of life in elderly patients, who are the largest users of dentures. Purpose: This article aims is to review the epidemiology, etiology and contributing factors, and management of complete denture fractures. Review Summary: Various studies show that fractures most often occur within first two to four years of the denture age, especially in the mandible and midline area due to flexural fatigue. The main causes include poor fit, unbalanced occlusion, fall trauma, and material defects such as porosity or an overly thin base. Repairs can be made using autopolymerizing resin, heat-cured resin, microwave polymerization, or visible light-cured resin, with reinforcement techniques such as E-glass fiber reinforcement, which has been shown to increase denture strength. Prevention focuses on proper design, good stress distribution, occlusal balance, and regular monitoring. Conclusion: A clear understanding of the etiology and fracture patterns is essential to improving clinical outcomes in denture fracture management. Strengthening clinical protocols through better diagnostic awareness and preventive strategies can help reduce the overall risk of denture fractures.